Improving, Restoring, and Managing Natural Resources on Rural Properties in Florida: Sources of Financial Assistance - Chris Demers; Martin B. Main; Mark E. Hostetler (EDIS)
Interested in conserving natural resources, such as wildlife habitat, on your land? Federal and State Governments have several programs to respond to a broad range of natural resource challenges faced by landowners. These programs help landowners to reduce soil erosion, protect wetlands and wildlife habitat, and promote forest and farmland productivity and protection. These challenges are addressed through land rentals, technical assistance, cost-shares, and incentive payments. This document is SS-FOR-23, one of a series of the School of Forest Resources and Conservation Department, UF/IFAS Extension. Original publication date February 2006.